2022
DOI: 10.3390/biom12111593
|View full text |Cite
|
Sign up to set email alerts
|

Pregnenolone Reduces Stress-Induced Craving, Anxiety, and Autonomic Arousal in Individuals with Cocaine Use Disorder

Abstract: Chronic cocaine use leads to adaptations in stress biology and in neuroactive steroid system. These adaptations are associated with high cocaine craving and increased relapse risk. This study tested whether potentiation of the neuroactive steroid system with the precursor pregnenolone (PREG) affects stress- and cue-induced cocaine craving, anxiety and autonomic response in individuals with cocaine use disorder (CUD). Thirty treatment-seeking individuals (21 Male, 9 Female) with CUD were randomized to placebo (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Other findings showed that pregnenolone and its GABAergic metabolites regulate alcohol motivation by reducing alcohol seeking and intake in rodents [52][53][54]. These results were confirmed in clinical studies in patients with history of cocaine and alcohol use disorders [55,56]. However, the data presented in this study suggest a negative interaction between 3α,5α-THP and the opioid system that might result in a deleterious behavior.…”
Section: Discussionsupporting
confidence: 82%
“…Other findings showed that pregnenolone and its GABAergic metabolites regulate alcohol motivation by reducing alcohol seeking and intake in rodents [52][53][54]. These results were confirmed in clinical studies in patients with history of cocaine and alcohol use disorders [55,56]. However, the data presented in this study suggest a negative interaction between 3α,5α-THP and the opioid system that might result in a deleterious behavior.…”
Section: Discussionsupporting
confidence: 82%
“…Pregnenolone supplementation significantly increases pregnenolone levels and effectively reduces stress and cocaine cueinduced craving and anxiety in individuals with CUD. Additionally, it demonstrates a notable reduction in stress-induced autonomic arousal [226].…”
Section: Substance Use Disordersmentioning
confidence: 97%
“…For many years, neurosteroids have been proposed as a therapy to restore altered GABAergic transmission in conditions such as depression, PTSD, PPD, anxiety, and substance use disorders [11][12][13]61,225,226]. These neuropsychiatric conditions share, among other features, a dysregulation in hypothalamic-pituitary-adrenal (HPA) axis activity [44,46,[227][228][229][230][231][232][233], likely due to aberrant GABAergic signaling [234,235].…”
Section: Neurosteroids and Neuroimmune Regulation 21 Neurosteroids: A...mentioning
confidence: 99%
“…[142][143][144] Remarkably, chronic treatment with supraphysiological doses of PREG reduces both stress-and cocaine cue-induced craving in individuals with cocaine use disorder. 145 PREG also acts as a potent negative allosteric modulator of CB1 receptor signaling 22 and blocks all the phenotypic signatures of cannabinoid intoxication. 22 However, at this stage, we could speculate that the rescue properties of PREG in PCE progeny cannot be ascribed to a negative modulation of CB1 receptor, but rather to its intracellular signaling.…”
Section: Pregnenolone Restores Pce Male Dopamine Function and Rescues...mentioning
confidence: 99%
“…Although the effects of σ1 receptor activation on dopamine system are conflicting, their ligands (including PREG) have been shown to attenuate dopamine signaling deregulation in response to psychostimulant drugs 142–144 . Remarkably, chronic treatment with supraphysiological doses of PREG reduces both stress‐ and cocaine cue‐induced craving in individuals with cocaine use disorder 145 . PREG also acts as a potent negative allosteric modulator of CB1 receptor signaling 22 and blocks all the phenotypic signatures of cannabinoid intoxication 22 .…”
Section: Pregnenolone Restores Pce Male Dopamine Function and Rescues...mentioning
confidence: 99%